A Multidisciplinary Look at Menopause 2017
DOI: 10.5772/intechopen.69078
|View full text |Cite
|
Sign up to set email alerts
|

Psychological and Social Aspects of Menopause

Abstract: Menopause is one of the age-related phases of physiological transition of females. There is robust research and information regarding its biological aspects specially its endocrine base, yet the psychosocial aspect is quite interesting and debatable due to its variability among diferent cultures and climates. There are certain subthreshold response in form fear and loss of reproductive life to no more ability to reproduce and a feeling of loss of femininity. The period of menstruation simulated to reproductive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 19 publications
1
11
0
Order By: Relevance
“…Menopause is defined as the time in a woman’s life when there has been no menstrual period for 12 consecutive months [ 1 ]. Although menopause is a normal and natural physiological process in a woman’s life, it can negatively affect [ 2 , 3 ] the one-third of their lifetime after menopause [ 4 ]. Studies have shown the negative impacts of menopausal symptoms on health-related quality of life (HRQOL) [ 5 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…Menopause is defined as the time in a woman’s life when there has been no menstrual period for 12 consecutive months [ 1 ]. Although menopause is a normal and natural physiological process in a woman’s life, it can negatively affect [ 2 , 3 ] the one-third of their lifetime after menopause [ 4 ]. Studies have shown the negative impacts of menopausal symptoms on health-related quality of life (HRQOL) [ 5 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…In this case, menopause is not considered a high-risk phase for psychiatric illness; however, it can be a time of psychological stress that, if not properly monitored, can evolve into a mood disorder, such as depression. 35 In the scientific literature, there is a debate regarding climacteric stages and their association with emotional state. In some studies, premenopausal women show greater depressive symptoms than postmenopausal women.…”
Section: Discussionmentioning
confidence: 99%
“…This can add irritability, which is the most frequent problem and the one that most affects social activities. 6,7 Vasomotor symptoms: hot flashes and night sweats constitute the most characteristic clinical manifestations of the climacteric, affecting the quality of life, even decreasing libido, causing irritability, fatigue, an embarrassment in public, anxiety, and depression.…”
Section: Psychological Changes In Climacteric and Menopausementioning
confidence: 99%